HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR KETERAMPILAN BOLAVOLI PADA SISWA DI SDN 28/VI SUMBER AGUNG I - Sugianto, Edi; Ismi Mori Saputra, Deka (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract In this research, the problem found by the author through observations made was the low learning outcomes of basic volleyball skills. This research aims to find out whether there is a relationship between motivation and learning outcomes for volleyball skills among students at SDN 28/VI Sumber Agung I. This type of research is correlational. The population in this study was 26 students at SDN 28/VI. The sampling technique uses total sampling. Thus, the sample in this study was 26 people. To collect motivation data, it is obtained from the results of distributing questionnaires to students. Meanwhile, basic volleyball skills are obtained from the results of the basic volleyball skills test. And the data is analyzed using product moment correlation. The data obtained from the research results show that the hypothesis in this research is that there is a significant relationship between motivation and the learning outcomes of volleyball skills for students at SDN 28/VI Sumber Agung I with an rhitung 0,483 > rtabel 0,320. Keywords: Motivation, Learning Outcomes, Volleyball Skills